Upaya Penguatan Kepercayaan Diri Remaja sebagai Citizen Journalist melalui Program Bina Desa di Kampung Pekijing - Siti Aynaya; Bangun Yoga Wibowo; Rochani Rochani (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
The Bina Desa program is a community service initiative aimed at empowering local potential through active community involvement, particularly among adolescents. This program was implemented in Kampung Pekijing, Kalang Anyar Village, Taktakan District, Serang City, which has been designated as a Literacy Tourism Village. The main problem identified was the limited involvement of adolescents in supporting village branding, especially in terms of self-confidence and communication skills. This program aimed to strengthen adolescents’ self-confidence as citizen journalists in supporting the branding development of Kampung Wisata Literasi Pekijing. The methods used included field observation, coordination with community and youth leaders, educational seminars, simulation activities for public speaking and camera performance, and evaluation through pretest and posttest. The results indicated an improvement in adolescents’ understanding and confidence in expressing themselves both verbally and through video media. This training had a positive impact on adolescents’ psychosocial readiness to actively participate as citizen journalists. Therefore, the Bina Desa program proved effective as an initial intervention to strengthen adolescents’ roles and to support literacy-based village branding.